2017
DOI: 10.1038/srep41310
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced performance of the microalga Chlorella sorokiniana remotely induced by the plant growth-promoting bacteria Azospirillum brasilense and Bacillus pumilus

Abstract: Remote effects (occurring without physical contact) of two plant growth-promoting bacteria (PGPB)Azospirillum brasilense Cd and Bacilus pumilus ES4 on growth of the green microalga Chlorella sorokiniana UTEX 2714 were studied. The two PGPB remotely enhanced the growth of the microalga, up to six-fold, and its cell volume by about three-fold. In addition to phenotypic changes, both bacteria remotely induced increases in the amounts of total lipids, total carbohydrates, and chlorophyll a in the cells of the micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 76 publications
0
50
0
2
Order By: Relevance
“…Algae were shown to benefit from micro-and macronutrients provided by bacteria, and in return, release dissolved organic carbon into their surroundings. Efforts have been made in identifying bacteria that positively contribute to the algal fitness; especially nitrogenfixing bacteria of the genera Azospirillum, Rhizobium, and Bacillus, known for their beneficial effect on plants, are promising candidates (Gonzalez and Bashan, 2000;de-Bashan et al, 2008;Hernandez et al, 2009;de-Bashan and Bashan, 2010;Kim et al, 2014;Amavizca et al, 2017). While binary algaebacteria interactions were explored in the past, little is known about the algae-associated microbiota as well as potentially beneficial algae-microbe interactions with distinct members of the plant microbiota.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Algae were shown to benefit from micro-and macronutrients provided by bacteria, and in return, release dissolved organic carbon into their surroundings. Efforts have been made in identifying bacteria that positively contribute to the algal fitness; especially nitrogenfixing bacteria of the genera Azospirillum, Rhizobium, and Bacillus, known for their beneficial effect on plants, are promising candidates (Gonzalez and Bashan, 2000;de-Bashan et al, 2008;Hernandez et al, 2009;de-Bashan and Bashan, 2010;Kim et al, 2014;Amavizca et al, 2017). While binary algaebacteria interactions were explored in the past, little is known about the algae-associated microbiota as well as potentially beneficial algae-microbe interactions with distinct members of the plant microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Mutualistic inter-kingdom symbioses are not only limited to land plants, but also extend to green algae (Xie et al, 2013;Hom et al, 2015). Following the same principles of plant growth-promoting rhizobacteria, algae-associated bacteria harbor potential to stimulate growth and morphogenesis of algae by releasing essential minerals, vitamins, auxins and quorum sensing signaling molecules (Joint et al, 2002;Croft et al, 2006;Goecke et al, 2010;Amavizca et al, 2017). The equivalent to the rhizosphere -the immediate surrounding of roots with increased biological and chemical activity in soil -is the phycoscphere, which is the area surrounding a phytoplankton cell, rich in dissolved organic matter and metabolites exuded by the cell in the surrounding water and stimulating the growth of heterotrophic bacteria (Seymour et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Esters such as methyl isobutyrate, EI, methyl 2‐methylbutanoate, and methyl 3‐methylbutanoate are emitted by Actynomycetes and Streptomyces (Schöller, Gürtler, Pedersen, Molin, & Wilkins, ; Schulz & Dickschat, ). IA, among several other volatiles, was produced by Azospirillum brasilense , Bacillus pumilus , and Escherichia coli in interaction with the microalga Chlorella sorokiniana , enhancing its performance (Amavizca et al, ). EV has been reported both in bacteria and fungi.…”
Section: Discussionmentioning
confidence: 99%
“…5. These data refer to the wastewater treatment performance promoting microalgal growth through providing nutrients, vitamins, phytohormones, chelators, or volatile organic compounds 12)- 16) , or by creating a favorable microenvironment 17) . Some previous studies have demonstrated through the cultivation of E. gracilis.…”
Section: Nutrient Removal During E Gracilis Cultivationmentioning
confidence: 99%